Insights Into the Early Gene Regulatory Network Controlling Neural Crest and Placode Fate Choices at the Neural Border - Seal, Subham; Monsoro-Burq, Anne H. (Frontiers in Physiology, 2020)
The neural crest cells and cranial placodes are two ectoderm-derived innovations in vertebrates that led to the acquisition of a complex head structure required for a predatory lifestyle. The neural crest gives rise to a vast array of tissues and cell types such as peripheral neurons and glial cells, melanocytes, secretory cells as well as cranial skeletal and connective cells. Together with cells derived from the cranial placodes, which contribute to sensory organs in the head, the neural crest also forms the cranial sensory ganglia. Neural crest and placodes both originate from the neural border, a portion of the ectoderm located between the neural plate, located medially, and the lateral non-neural ectoderm. Multiple in vivo studies in different model systems have uncovered the signaling pathways and genetic factors that govern the positioning, development and differentiation of these tissues. In this literature review, we give an overview of neural crest and placode development, focusing on the early gene regulatory network that controls the formation of the neural border during early embryonic stages, and later dictates the choice between the neural crest and placode progenitor fates.